"And of the Croats who arrived to Dalmatia one part separated and ruled Illyricum and Pannonia". Remarks about the De administrando imperio c. 30, 75-78 - Gračanin, Hrvoje (2009)
The author endavours to discuss anew a historiographic problem pertinent to the Croatian early middle ages and centred on a few lines from Constantine VII. Porphyrogennetus's De administrando imperio: And of the Croats who arrived to Dalmatia one part separated and ruled Illyricum and Pannonia. But they also had an autonomous ruler who was sending embassies, but only to the ruler of Croatia from friendship. In a nutshell, the main question examined here is whether the Croats or, better yet, the fundamental ethnic group or groups which participated decisively in the Croatian ethnogenesis already settled in the Southpannonian area in the 7th century A.D., or this, in all its value, cannot be the case, that is to say, should the presence of the Croatian ethnie in the Sava-Drava-Danube interamnium in the early middle ages be rather seen as a result of unsufficiently substantiative conjectures of modern researchers. The paper argues that the view supporting such an early presence of the Croats in South Pannonia is misleading, and if there were any Croats there at all, their number must have been negligible when compared to the other Slavic populations, which is also very much in consistency with the fact that the area of the primary Croatian ethogenesis was much farther to the south, close to the Adriatic.